An experimental investigation of the performance of new design of solar air heater (tubular). (May 2020) - Hassan, Hamdy; Abo-Elfadl, Saleh; El-Dosoky, M.F.
Abstract: An experimental work on the performance of new design of solar air heater (SAH) called tubular solar heater (TSAH) is investigated experimentally. In this design, the flat absorber plate of the flat solar air heater (FSAH) is replaced by adjacent tubes at the same direction of the airflow through the SAH. Two SAHs (FSAH and TSAH) having the same dimensions and materials except their absorbers are constructed to compare their performance at different airflow rates through the SAHs. Results reveal that the TSAH has higher efficiency, output power, and outlet air temperature and lower top heat loss compared to FSAH. Moreover, it is found that the efficiency of the presented TSAH is greater than the efficiency of the studied previous SAHs designs. TSAH achieves a maximum rise of 13.2 °C for the outlet air temperature from the SAH compared to FSAH at inlet air mass flow rate 0.025 kg/s to the SAHs. The average daily TSAH efficiency is about 83.6%, 76.3% and 59.8% at air mass flow rate 0.075, 0.05 and 0.025 kg/s, respectively with an increase of 132.6%, 58.6%, and 43.5%, respectively compared to FSAH. The daily top heat loss of TSAH decreases by about 10% compared to FSAH. Highlights: New design of the solar air heater (tubular SAH) is presented experimentally. TSAH achieves maximum air temperature rise of 13.2 °C compared to FSAH at 0.025 kg/s. Average daily efficiency of TSAH increases by 132.6% compared to the FSAH at 0.025 kg/s. Efficiency of present TSAH is greater than efficiency of the previous presented SAHs designs. Pressure drop of the TSAH is greater than FSAH but hasn't an effect on the net results.